EVALUASI KINERJA JARINGAN JALAN EKSISTING KOTA SURAKARTA DENGAN SKENARIO DO SOMETHING - Indra Pradana, Doni; Syafi'i, Syafi'i; Jauhari Legowo, Slamet (Matriks Teknik Sipil, 2014)
AbstractSurakarta is located in the province of Central Java, the total area is 44 km2, inhabited by a population of 578.892 inhabitants (2013).Growth in the number of vehicles that are not balanced by the growth of road length will result in saturation points due to traffic delays. This studyaim to evaluate the performance of the road network Surakarta in 2013 based on the value of the Volume Ratio and Capacity ( NVK ). NVKobtained by comparing the volume of traffic to road capacity. Traffic volume matrix obtained by assigning Origin Destination (OD) Matrix to theroad network with the help of software EMME/3. Capacity is calculated based Manual Kapasitas Jalan Indonesia (MKJI). NVK value < 0,8is a stable condition, the value of 0,8-1 called unstable condition, if the value of NVK >1 then the road are in critical condition. NVK road with?0,8 given the solution to the handling of side friction reduction scenario by restricting on street parking and prohibit activities on the soulder of theroad pavement. In condition do nothing NVK value on road that are included in the range of 0,8-1 is 6,04%, the value of NVK ?1 IS 3,83%.After handling scenario such as parking prohibition and prohibition of actifities in the shoulder of the road pavement, the value of NVK 2013condition do something road NVK are included in the range of 0,8-1 down to 4,76%, the value of NVK ? 1drop to 3,02%.